Selected genetic factors increasing risk of neoplasia - Niewiadomski, Paweł; Mikołajczyk, Klaudia; Rauhut, Sebastian; Stryjak, Krzysztof; Lazarek, Maciej; Olszewski, Bogusz; Sochań, Agata; Kędziora-Kornatowska, Kornelia (Journal of Education, Health and Sport, 2019)
Introduction: Neoplasia is defined as abnormal and excessive growth of selected tissue. Several factors, such as mutations in selected genes, can increase the risk of cancer expansion in human body. The aim of the article is to review the selected genetic factors which increase the risk of neoplasia and results of their presence in the human body.Material and methods: Articles in the Google Scholar, Pub Med database have been analysed using keywords: cancer, neoplasia, genetic factors, driver genes, cancer transformation, older people.Results: The aim of several genes is repairing damaged or dysfunctional DNA and preventing cells from abnormal or excessive. Mutations in selected genes cause inhibited production of the gene protein product or a change in its function, which increase the risk of neoplasia. The presence of mutated genes results in the initiation of the process leading to expansion of cancer cells in selected tissue. Moreover, a genetic mutation can lead to syndrome of tumors occurring in several organs. However, the increasement of cancer risk is related to numerous mutations, whereas the minority of carcinomas occur because of congenital gene defect and the majority is caused by environmental factors which contribute to creating various mutations.Conclusions: Thanks to the development of genetics in the field of medicine and introduction of genetic tests, the process of diagnosis of several tumors and syndromes is more efficient than in the past. The occurrence of mutation in genes, such as BRCA1, BRCA2, VHL, MSH2 and MLH1 and many more, relates to presence of selected tumors. By the introduction of pharmacogenetics, dozens of molecular-targeted drugs are used in the treatment of several types of cancers leading the achievement of therapeutic success. Nevertheless, the genetic background of many types of cancers is unknown and needs further study, as well as drugs targeting at selected genes mutations requires more development and guidelines in the treatment process.Keywords: cancer; neoplasia; genetic factors; driver genes; cancer transformation; older people;